Nutritional Status Of Primary School Children In Rural Area Of Dehra Dun - Semwal, Jayanti; Kishore, Surekha; Negi, K S; Saxena, P; Kar, Sonali (Indian Journal of Community Health, 2004)
To assess the Nutritional status of primary school children. To compare these values with ICMR and NCHS standards. To assess any significant differnce between nutritional status of boys and girls. Study disigan : Cross- sectional, school based study. Setting : Five Govt primary schools. Study variables : Age, Sex, Weight. Height and BMI. Statistical Analysis : percentile, mean, standard deviation, T test, 'z' tests. Result : In all age groups the nutritional status of boys and girls was found lower then the NCHS standards. Mean height and weight in both sexes were comparable to ICMR 50th percentile weight was higher in boys than ICMR values with increasing age except in 5 year and 11 year age group. BMI in girls in age group 10, 11 and 12 years is found to be better than boys. Mean weight of girls is better than boys in age group 11 and 12 years but statistically insignificant.